Use of Annexin V based Sperm Selection in Assisted Reproduction - Teijeiro, Juan Manuel (2017)
Fil: Fil: Munuce, María José. Universidad Nacional de Rosario. Facultad de Ciencias Bioquímicas y Farmacéuticas. Laboratorio de Medicina Reproductiva; Argentina.